The psychosocial impact of surgical complications on the operating surgeon: A scoping review. (July 2021) - Siddaiah-Subramanya, Manjunath; To, Henry; Haigh, Catherine
Abstract: Background and Aim: Surgical complications are common, and their management is an integral part of surgical care. The impact on the surgeon, the "second victim" is significant, particularly in terms of psychological health. The aim of this review is to describe the nature of psychosocial consequences of surgical complications on the surgeons involved. Method: Following scoping review protocols, we set out to identify the evidence-base for psychosocial consequences on the operating surgeon, predominantly general surgeons, following surgical complications. Results: This scoping review identified 19 articles, mainly survey and interview based (n = 8), with all but one article from first world countries. Seven articles reported on negative emotions or depressive behavioural responses. All original studies reported on difficulty in coping (37.5%), and a range of behaviours. There was little evidence for support structures or active interventions to aid the surgeon post complication. Conclusions: The review suggests that the psychosocial impact, following a complication, is variable but affects every surgeon irrespective of the level of impact on the patient. The main variables differentiating impact are severity, and outcome of the complication and seniority of the surgeon. Reported emotions and behaviours were generally negative and persist across the surgeon's journey towards recovery. Surgeons who manage stress well exhibit largely constructive behaviours and actively work to recover. Identification of variables underpinning complications, and affected surgeons is paramount, as is the provision of services to support recovery. Efforts should be made to proactively prevent complications, via education, awareness and to formalise support processes. Highlights: Surgical complications negatively impact the operating surgeon (the second victim). Negative emotions and behaviours manifested may persist throughout surgeon's career. Surgeons' reaction can negatively influence social and professional relationships. Range of factors affect coping and recovery, and the support sought tend not to focus on psychosocial aspects of coping. Need to develop management resources for surgeons to manage the psychosocial impact.